KOMUNIKASI HIPNOTERAPI DALAM PENYEMBUHAN FOBIA KLIEN DI KLINIK ISAM CAHAYA HOLISTIC CARE MAKASSAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
This study discusses hypnotherapy communication in phobia healing in the Isam Cahaya Holistic Care Makassar clinic and the obstacles experienced by hypnotherapists in healing phobic clients. This type of research uses qualitative research with descriptive type. Informants in this study are hypnotherapy practitioners and clients in the Isam Cahaya Holistic Care clinic in Makassar. Based on the results of this study indicate that the stages of hypnotherapy communication in healing phobias at the Isam Cahaya Holistic Care Makassar clinic is to use interpersonal communication with dyadic communication forms and several stages of hypnosis in communication processes sometimes using two-way communication patterns and one-way communication patterns, while obstacles experienced by the hypnotherapist in healing his client's phobias such as psychological barriers and semantic barriers.